Variations of LÃƒÂ¢Ã‹â€ Ã¢â‚¬â€aÃƒÂ¢Ã‹â€ Ã¢â‚¬â€bÃƒÂ¢Ã‹â€ Ã¢â‚¬â€ Values among Vitapan Classical Shade Guides - Kenneth A. King, DDS;1 and Waldemar G. deRijk, MS, PhD, DDS2 (Journal of Prosthodontics, 2007)
To measure the variations in LÃƒÂ¢Ã‹â€ Ã¢â‚¬â€aÃƒÂ¢Ã‹â€ Ã¢â‚¬â€bÃƒÂ¢Ã‹â€ Ã¢â‚¬â€ values of a group of 25 guides and to assess whether shade guides are indeed interchangeable